Size and shape determination of an experimental unit, with the maximum curvature method, for corn (Zea mays) yield trials, Guanacaste, Costa Rica (UNED Research Journal, 2017)
A study was conducted to determine the adequate size and shape of an experimental unit for corn yield trials in the canton of Santa Cruz, Guanacaste, Costa Rica. A uniformity trial was seeded and the data obtained were used to apply the method of maximum curvature. The point of maximum curvature – determined by visual inspection – where the curve, product of the association between plot size and coefficient of variation stops falling abruptly and taking an almost constant behavior, was located between 12 and 16 basic units. Through the first derivative, it was estimated that the point of maximum curvature was 12 basic units. Using the method proposed by Fairfield Smith in 1938, a value of 0.62 for the soil heterogeneity index was obtained, indicating the soil can be classified as heterogeneous (the area of this measurement scale goes from 0 to 1, where 0 indicates complete homogeneity and 1 complete heterogeneity). There was no difference between the forms associated with the size of 12 basic units; however, for practical reasons, the form of 6 X 2 was considered the most suitable.
Keywords: plot size; plot shape; corn; maximum curvature method; soil heterogeneity; Smith´s index.